Analysis of Factors Influencing Talent's Decision to Stay or Leave the Organization in the Talent War Situation: A Case Study of PT. Tambang Indonesia - Sari Mulatsih; Mone S. Andrias (International Journal of Science and Society, 2023)
In the era of the talent war in the coal mining industry that has occurred from 2022 to 2023, talent retention is one of the keys to success for companies in the industry, including mining contractor companies. This study aims to examine talent retention by exploring how several factors influence the talent's decision to stay or leave an organization in a talent war situation. This research was conducted using qualitative methods with a single case study on PT Tambang Indonesia. Data collection was carried out through in-depth interviews with 29 informants and document analysis which was analyzed using thematic analysis. The main findings of this research are four pull forces that influence talent's decision to stay and four push forces that influence talent's decisions to leave in a talent war situation. The supporting findings in this research are talent retention factors at three levels of organizational behavior analysis. The findings in this study deepen previous studies regarding factors in talent retention. Suggestions for further research are to make research that can measure each force, and then be tested in a wider and more diverse context. Further research can also be conducted with a focus on measuring the level of influence of factors at three levels of organizational behavior analysis, as well as comparing the effectiveness of these factors on talent retention.